1991
DOI: 10.1159/000112169
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Function in Adult Adrenoleukodystrophy: Comparison with Leukoaraiosis and Multiple Sclerosis

Abstract: Cognitive evaluation of 6 cases of adult adrenoleukodystrophy (ALD) included in a brain magnetic resonance (MR) study are reported: 2 males with adrenomyeloneuropathy and 4 women heterozygous for ALD. Cognition was normal in 4 and MR scan in 2 of them. In the 2 others, there were mild modifications of the white matter. One patient suffered of visual retention disturbances with abnormalities of the white matter in MR scan. In the last, cognitive decline was observed; MR scan showed atrophy of cortex and corpus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…108, 109, 110, 111, 112, 113, 114, 115, 116, 117, 118, 119, 120, 121, 122, 123, 124, 125, 126, 127, 128, 129, 130, 131, 132, 133, 134, 135, 136, 137, 138, 139, 140, 141, 142, 143, 144 In most lipid storage diseases of the nervous system (neurolipidoses) or leukodystrophies, which can present at some point with acute, progressive or relapsing psychosyndromes (Tay–Sachs and Sandhoff disease, Fabry disease, metachromatic leukodystrophy, adrenoleukodystrophy, Niemann–Pick type C, ceroid neuronal lipofuscinoses), pharmacotherapy of psychiatric manifestations has either poor effect or even worsens the condition, for example, as in adult-onset GM 2 gangliosidoses, where phenothiazines and tricyclic antidepressants may have a detrimental effect by inhibiting the activity of lysosomal enzymes, thereby increasing lipid storage in neuronal cells. 115, 116, 117, 118, 119, 120, 121, 122, 123, 124, 125, 126, 127, 128, 129, 130, 131, 132, 133, 134, 135, 136, 137, 138, 139, 140, 141, 142, 143 This is a little known domain of neuropsychiatry, because neurodegenerative/neurometabolic diseases are rare and seldom end up in the principal care of the psychiatrist. 8, 115, 117, 134, 142 The latter happens when these conditions present either as complex neu...…”
Section: Discussionmentioning
confidence: 99%
“…108, 109, 110, 111, 112, 113, 114, 115, 116, 117, 118, 119, 120, 121, 122, 123, 124, 125, 126, 127, 128, 129, 130, 131, 132, 133, 134, 135, 136, 137, 138, 139, 140, 141, 142, 143, 144 In most lipid storage diseases of the nervous system (neurolipidoses) or leukodystrophies, which can present at some point with acute, progressive or relapsing psychosyndromes (Tay–Sachs and Sandhoff disease, Fabry disease, metachromatic leukodystrophy, adrenoleukodystrophy, Niemann–Pick type C, ceroid neuronal lipofuscinoses), pharmacotherapy of psychiatric manifestations has either poor effect or even worsens the condition, for example, as in adult-onset GM 2 gangliosidoses, where phenothiazines and tricyclic antidepressants may have a detrimental effect by inhibiting the activity of lysosomal enzymes, thereby increasing lipid storage in neuronal cells. 115, 116, 117, 118, 119, 120, 121, 122, 123, 124, 125, 126, 127, 128, 129, 130, 131, 132, 133, 134, 135, 136, 137, 138, 139, 140, 141, 142, 143 This is a little known domain of neuropsychiatry, because neurodegenerative/neurometabolic diseases are rare and seldom end up in the principal care of the psychiatrist. 8, 115, 117, 134, 142 The latter happens when these conditions present either as complex neu...…”
Section: Discussionmentioning
confidence: 99%
“…Despite profoundly improved MRI techniques, clinical characterization of the disease via structural imaging criteria is still missing. In particular the prevalence of cognitive disorders in this inhomogeneous patient group seems to be far from predictable [11]. …”
Section: Introductionmentioning
confidence: 99%
“…65,66 While overall IQ is typically preserved, mild or isolated impairments in specific neurocognitive domains have been noted, most frequently within the domains of executive function, [66][67][68] visuoconstruction, 67,69 verbal fluency, 67,69 and memory. [68][69][70] Psychomotor slowing has also been reported. 67,68 In a sample of 33 men with ALD and no cerebral involvement, Buermans and colleagues reported that 6 patients (18%) had borderline to impaired scores in two cognitive domains and 3 patients (9%) had borderline or impaired scores in three cognitive domains.…”
Section: Adult Non-cerebral Phenotype and Adrenomyeloneuropathymentioning
confidence: 90%
“…Generally, in the absence of cerebral involvement, men with ALD or AMN tend to have intact intellectual functioning 65,66 . While overall IQ is typically preserved, mild or isolated impairments in specific neurocognitive domains have been noted, most frequently within the domains of executive function, 66–68 visuoconstruction, 67,69 verbal fluency, 67,69 and memory 68–70 . Psychomotor slowing has also been reported 67,68 .…”
Section: Males With Aldmentioning
confidence: 99%